Cytokines and dietary energy restriction in stable chronic obstructive pulmonary disease patients - Godoy, Irma de [UNESP]; Campana, A. ́ O [UNESP]; Geraldo, R. R C [UNESP]; Padovani, Carlos Roberto [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP] (European Respiratory Society (ERS), 2003)
Tumour necrosis factor (TNF)-α has been found to be increased in malnourished chronic obstructive pulmonary disease (COPD) patients; however, the main cause of this phenomenon remains undetermined. In normal subjects, TNF-α production may be induced by dietary energy deprivation. The aim of this study was to investigate if stable COPD patients present alterations of inflammatory mediators after 48 h of dietary energy restriction. Fourteen COPD patients were admitted to the hospital while receiving an experimental diet with an energy content of approximately one-third of their energy needs. Clinical evaluation, nutritional assessment and serum levels of interleukin (IL)-6, TNF-α and C-reactive protein, and secretion of TNF-α by peripheral blood monocytes were assessed on admission and after the experimental diet. For reference values of the laboratory parameters, blood was collected from 10 healthy, elderly subjects. COPD patients showed significantly higher serum concentrations of IL-6 than control subjects, however, the experimental diet was not associated with statistically significant changes in the inflammatory mediators. The findings of this study, although preliminary because of the limited degree and duration of the energy restriction, suggest that the elevated levels of tumour necrosis factor-α, previously described in undernourished or weight-losing chronic obstructive pulmonary disease patients, may not be linked to a decrease of dietary energy intake.
Keywords: Chronic obstructive pulmonary disease; Cytokines; Energy restriction; Interleukin-6; Malnutrition; Tumour necrosis factor-α; C reactive protein; cytokine; interleukin 6; tumor necrosis factor alpha; adult; aged; blood sampling; body composition; caloric intake; cell culture; cell isolation; chronic obstructive lung disease; clinical article; controlled study; cytokine production; cytokine release; diet restriction; female; forced expiratory volume; human; lung function test; male; malnutrition; monocyte; nutritional parameters; priority journal; protein blood level; smoking habit; statistical significance; Aged; Anthropometry; C-Reactive Protein; Caloric Restriction; Female; Hospitalization; Humans; Male; Middle Aged; Monocytes; Nutritional Status; Pulmonary Disease, Chronic Obstructive; Tumor Necrosis Factor-alpha